1972
DOI: 10.1111/j.1432-1033.1972.tb01906.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prostaglandins in the Gorgonian, Plexaura homomalla

Abstract: Hexane extracts of the air-dried cortex of the gorgonian Plexaura homomalla (Esper) were found to contain (15R)-hydroxy-9-oxo-prost-5,10,13-trienoic acid [i.e. (15R)-prostaglandin A,] and its 15-acetate methyl ester in 0.Zo/, and 1.3O/, yield from the cortex by Weinheimer and Spraggins in 1969. Chloroform-methanol extracts of this organism have now been shown to contain these two compounds as major prostaglandin constituents, but also a more complex mixture of prostaglandin derivatives including lln,(l5R)-dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…These compounds possessed the nonmammalian R configuration at CI5 and lacked the vasodilatory effect of the mammalian PGA, in vivo. Similar findings were reported by others (Light & Samuellson 1972) for the same species. Bundy et al (1972) demonstrated that these inactive compounds could be chemically modified to yield biologically active products.…”
Section: Prostaglandins In Aquatic Invertebratessupporting
confidence: 81%
“…These compounds possessed the nonmammalian R configuration at CI5 and lacked the vasodilatory effect of the mammalian PGA, in vivo. Similar findings were reported by others (Light & Samuellson 1972) for the same species. Bundy et al (1972) demonstrated that these inactive compounds could be chemically modified to yield biologically active products.…”
Section: Prostaglandins In Aquatic Invertebratessupporting
confidence: 81%
“…Further acetylation gives the PGA 2 methyl ester 15-acetate, which then accumulates in the coral. This explains why the 15-acetate of PGA 2 is found in P. homomalla, but PGE 2 occurs only as the methyl ester (1)(2)(3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments designed to reduce the prostaglandin endoperoxide in situ and to simplify the pattern of products, 0.5 mM SnCl 2 was added to the incubation mixtures just before [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]arachidonic acid. This gave an immediate reduction of the peroxy intermediates to the corresponding hydroxy compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the inhibition of intermediates was studied, SnCl 2 (final concentration, 0.5 mM) was added into the incubation mixture. Values are means Ϯ S. D., n ϭ 3. q, total PGs formed in incubations without the reducing agent; f, PGF 2␣ ; OE, ( homomalla, but the latter also contains esters of PGE 2 and PGF 2␣ (25,26), and it now seems to be much more likely that the PGA derivatives are formed from the PGE derivatives rather than the other way around. The isolation of PGG 2 from short incubations of G. fruticosa gave a strong evidence that prostaglandins are synthesized via the endoperoxide pathway (13).…”
Section: Effect Of Inhibitors On Arachidonic Acid Metabolism In G Frmentioning
confidence: 99%